2019
DOI: 10.1002/prep.201900250
|View full text |Cite
|
Sign up to set email alerts
|

RDX Based Enhanced Energy Propellant for Tank Gun Ammunition

Abstract: Ammunition designers are faced now a day with the tasks of improving muzzle velocity (MV) to achieve required penetration as well as developing gun propellant with minimum variation of ballistics at extremes of temperatures so as to maintain safe chamber pressure of gun. In order to meet the requirement an optimized propellant composition containing RDX, energetic plasticizer, nitrocellulose (NC), cellulose acetate (CA) and additives referred as Enhanced Energy Propellant (EEP) was processed and evaluated theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Concerning the composition, reduced sensitivity RDX appears to be a good candidate to reach LOVA requirements. We can also note the very recent study of Jaiswal et al [16] who formulate an enhanced energy propellant based on RDX and NC with better stability and thermal properties than conventional propellants.…”
Section: Introductionmentioning
confidence: 69%
“…Concerning the composition, reduced sensitivity RDX appears to be a good candidate to reach LOVA requirements. We can also note the very recent study of Jaiswal et al [16] who formulate an enhanced energy propellant based on RDX and NC with better stability and thermal properties than conventional propellants.…”
Section: Introductionmentioning
confidence: 69%
“…Examples of cyclic nitramines are the two secondary explosives hexogen (1,3,5trinitro-1,3,5-triazinane, RDX) and octogen (1,3,5,7-tetranitro-1,3,5,7-tetrazocane, HMX), both of which are mainly used in the military sector in warheads or propellant formulations. [23][24][25] In addition, there are also open-chain nitramine energetic compounds such as the nitroxyethyl nitramines (NENAs). Important examples of NENAs are BuNENA (n-butyl nitroxyethylnitramine) or DINA (dioxyethylnitramine dinitrate), both of which are used as plasticizers in propellant formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The nitramine functional group is also widely used as an energetic building block in energetic materials, and many compounds which incorporate this building block are known and show promise for use in applications. Examples of cyclic nitramines are the two secondary explosives hexogen (1,3,5‐trinitro‐1,3,5‐triazinane, RDX) and octogen (1,3,5,7‐tetranitro‐1,3,5,7‐tetrazocane, HMX), both of which are mainly used in the military sector in warheads or propellant formulations [23–25] . In addition, there are also open‐chain nitramine energetic compounds such as the nitroxyethyl nitramines (NENAs).…”
Section: Introductionmentioning
confidence: 99%
“…Overall it has been gathered from the literature that high energy materials such as RDX, HMX, FOX-7, and CL-20, when used in propellants, have given promising results. Reduced vulnerability, better output, and higher burning rate are some of the characteristics incorporated in the propellant compositions on the inclusion of high-energy materials [16][17][18]. In a recent study Wang et al [19] reported that burning rates of composite modified double base (CMDB) propellants increased substantially with the addition of CL-20 and decreased with the addition of RDX.…”
Section: Introductionmentioning
confidence: 99%
“…Overall it has been gathered from the literature that high energy materials such as RDX, HMX, FOX‐7, and CL‐20, when used in propellants, have given promising results. Reduced vulnerability, better output, and higher burning rate are some of the characteristics incorporated in the propellant compositions on the inclusion of high‐energy materials [16–18]. In a recent study Wang et al.…”
Section: Introductionmentioning
confidence: 99%